Internal model control (IMC) based tuning of PID controller for a non-adiabatic CSTR operating at unstable steady state - Prasad, Durga; Azmi Abu Bakar, Khairul; Kumar, Munna; Safie Mohd Satar, Nurhizam; Sriram, K.; Srivastav, Anupam; N. Upadhyay, S.; Sharan Singh, Ram (International Journal of Engineering and Technology, 2019)
Electronic customer relationship management (E-CRM) is a modern tool to secure and maintain competitive advantage that focuses on customers. Telecommunication companies nowadays are attentive to the employees, in their effort to enhance job satisfaction through the development of E-CRM. This study aims to integrate theories for a development model to enhance employee satisfaction in telecommunication companies that employed the method of summarizing theoretical reviews. This study contributed to the knowledge in the domain of E-CRM and the success factors in organizations. Therefore, it is important to improve a readily available model that combines every theory that correlated with the current study. The adopted model in telecommunication companies ensures the successful adoption of E-CRM that affects employee satisfaction and enhances individual performance. Additionally, this study contributed to the improvement of an integrated model that combines technology, organization, and individual factors influencing telecommunication companies in developing countries.